Preparation method of zirconite ramming material for glass kiln
By using cast zircon corundum powder and alumina in zircon ramming materials and using silicon sol-alumina composite cementitious agent, the problem of degradation of existing zircon ramming materials at high temperatures is solved, and high efficiency is achieved , low-cost zircon pounding material preparation meets the use requirements of glass kiln bottoms.
Patent Information
- Application Number
- CN202411553526.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-02
- Publication Date
- 2025-02-07
AI Technical Summary
The performance of existing zircon pounding materials decreases at high temperatures, which easily forms pores, affecting the quality of glass products. At the same time, the price of zircon remains high, resulting in high cost pressure.
Zircon is used as refractory aggregate, melt-cast zirconium corundum powder is used as refractory powder, alumina is used as additive, and silica sol-alumina composite cementing agent replaces the traditional silicate cementing agent, and glass kilns are prepared through high-pressure molding and low-temperature sintering processes. Use ramming material.
It improves the corrosion resistance and mechanical properties of zircon pounding materials, reduces high-temperature sintering and shrinkage, shows low porosity, meets the technical standards of zircon pounding materials, reduces costs and extends service life.
Smart Images

Figure BDA0005115730490000051
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of refractory materials, and in particular to a method for preparing zircon ramming mass for a glass furnace. Background Art
[0002] Ramming materials used as the sealing layer of the bottom of glass kiln generally need to have unique properties such as high thermal decomposition temperature, stable chemical properties, linear expansion coefficient, excellent thermal shock stability and corrosion resistance. Zircon has high refractoriness, low thermal expansion coefficient, good thermal shock stability and excellent resistance to erosion by molten steel and alkaline slag, and can be used as a high-grade refractory material. The current high demand for zircon at home and abroad has led to an increase in its price year by year, which has brought great cost pressure to refractory companies and glass companies.
[0003] With the increase of melting temperature of glass melting furnace and the development of overall sealing and heat preservation technology, the use environment of pool bottom ramming mass is becoming more and more harsh, and higher requirements are put forward for the corrosion resistance of ramming mass. Most of the zircon ramming mass reported so far uses phosphoric acid or phosphate as binder. Phosphate is easy to absorb moisture, and phosphoric acid or phosphate binder reacts with the components of ramming mass to form pores. In addition, phosphorus pentoxide is easy to transfer and volatilize to form low-melting products at high temperature, which reduces the performance of ramming mass at high temperature and will seriously affect the quality of glass products. Summary of the invention
[0004] In view of the problems existing in the background technology, in order to improve the quality of zircon ramming mass, extend the service life of zircon ramming mass, and reduce the cost of zircon ramming mass, the present invention provides a method for preparing zircon ramming mass for glass kiln, comprising the following steps:
[0005] (1) Ingredients: Weigh zircon bricks, zircon sand, fused-cast zirconium corundum bricks, additives and binders according to the number of parts. Break the fused-cast zirconium corundum bricks into pieces and put them into a nylon can. Grind them in a planetary mill for 48 hours, dry them and sieve them.
[0006] (2) Mixing: dry-mix zircon bricks, zircon sand and fused zirconium corundum bricks for 2 to 3 minutes, then slowly add additives and binders and wet-mix for 3 to 5 minutes, and then sieve to obtain a mixed material.
[0007] (3) Molding: The mixed material in step (2) is pounded into a crucible-shaped or cylindrical embryo under a pressure of 20 MPa.
[0008] (4) Drying: The embryo is dried with the mold at 125°C for 8 hours and then demolded.
[0009] (5) Sintering: After demoulding, place it in an electric furnace and sinter it at 1250-1400°C for 10 hours, then cool it to room temperature.
[0010] Preferably, 45 to 50 parts of zircon bricks, 12 to 18 parts of zircon sand, 15 to 23 parts of fused-cast zirconium corundum bricks, 7 to 14 parts of additives and 8 to 15 parts of binders are used.
[0011] Further preferably, the additive is one or more of alumina, magnesium oxide, boric acid, and cerium oxide, and the binder is a silica sol-alumina composite binder.
[0012] Preferably, the operating parameters of the planetary mill during grinding in step (1) are: orbital speed 250 r / min, rotational speed 200 r / min, ball: material = 15:1.
[0013] Preferably, in step (1), a certain amount of deionized water is added as a grinding medium to improve the grinding efficiency, and the mixture is dried and passed through a 120-mesh sieve.
[0014] Preferably, in step (2), the materials are mixed and then passed through a 4-mesh sieve.
[0015] Preferably, the mold size in step (3) is
[0016] Compared with the existing technical solutions, the present invention has the following beneficial effects:
[0017] The present invention adopts zircon as refractory aggregate, fused zirconium corundum powder as refractory powder, alumina as additive, and silica sol-alumina composite binder instead of traditional silicate binder to prepare ramming material for glass kiln. Alumina can improve the corrosion resistance of ramming material. Silica sol-alumina composite binder can be hardened at room temperature and has small sintering shrinkage, and forms a ceramic bonding phase mainly composed of mullite with uniform distribution and dense structure at the glass melting temperature. The high-temperature sintering shrinkage of ramming material is reduced, and the mechanical properties of the material are improved to a great extent.
[0018] In the preparation process, the present invention is formed under a pressure of 20MPa in order to avoid the deviation of sample density caused by manual ramming. In addition, in the sintering stage, the present invention is dried with the mold to avoid cracks that may occur during demoulding. The zircon ramming material obtained by this process has a low sintering temperature, a dense structure, low apparent pores, and high strength. It not only meets the technical standards of zircon ramming materials, but also improves the construction efficiency of the construction site, reduces the cost of zircon ramming materials, and meets the service life and construction requirements of the glass kiln pool bottom. DETAILED DESCRIPTION
[0019] The following embodiments of the technical solution of the present invention are described in detail in conjunction with the embodiments. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and are therefore only used as examples, and cannot be used to limit the protection scope of the present invention.
[0020] It should be noted that the experimental methods used in the implementation examples are all conventional methods unless otherwise specified; the materials, reagents, etc. used, unless otherwise specified, can be obtained from commercial channels.
[0021] In the present invention, unless otherwise specified, all "parts" and percentages (%) refer to percentages by weight.
[0022] In the present invention, unless otherwise specified, the sum of all percentages in all compositions is 100%.
[0023] In the present invention, unless otherwise specified, the numerical range "a-b" represents an abbreviation of any real number combination between a-b, where a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations.
[0024] In the present invention, unless otherwise specified, all embodiments and preferred embodiments mentioned herein can be combined with each other to form a new technical solution.
[0025] In the present invention, unless otherwise specified, all the steps mentioned herein may be performed sequentially or randomly, but are preferably performed sequentially; for example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially; for example, the method may further include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0026] In the present invention, unless otherwise specified, the specific numerical values and specific substances in the embodiments of the present invention may be combined with other features of the description part of the present invention; for example, if the specification mentions that the reaction temperature is 10-100°C, and the embodiment mentions that the reaction temperature is 20°C, then it can be considered that the present invention has specifically disclosed the range of 10-20°C, or the range of 20-100°C, and this range can be combined with other features of the description part to form a new technical solution.
[0027] Example 1
[0028] Weigh 50 parts of zircon bricks, 15 parts of zircon sand, 20 parts of fused zirconium corundum bricks, 7 parts of alumina, and 8 parts of silica sol-alumina composite binder. Break the fused zirconium corundum bricks into pieces and put them into a nylon jar. Use deionized water as the grinding medium and grind them in a planetary mill for 48 hours. After drying, pass through a 120-mesh sieve. Dry-mix zircon bricks, zircon sand, and fused zirconium corundum bricks for 3 minutes, then slowly add alumina and silica sol-alumina composite binder and wet-mix for 5 minutes, then pass through a 4-mesh sieve to obtain a mixture. Ram the mixture into a cylindrical embryo under a pressure of 20MPa. The embryo is dried at 125°C for 8 hours with the mold and demolded. After demolding, place it in an electric furnace, sinter it at 1250°C for 10 hours, and cool it to room temperature.
[0029] Example 2
[0030] Weigh 45 parts of zircon bricks, 16 parts of zircon sand, 23 parts of fused zirconium corundum bricks, 8 parts of alumina, and 8 parts of silica sol-alumina composite binder. Break the fused zirconium corundum bricks into pieces and put them into a nylon jar. Use deionized water as the grinding medium and grind them in a planetary mill for 48 hours. After drying, pass through a 120-mesh sieve. Dry-mix zircon bricks, zircon sand, and fused zirconium corundum bricks for 3 minutes, then slowly add alumina and silica sol-alumina composite binder and wet-mix for 4 minutes, then pass through a 4-mesh sieve to obtain a mixture. Ram the mixture into a crucible-shaped embryo under a pressure of 20MPa. The embryo is dried at 125°C with the mold for 8 hours and demolded. After demolding, place it in an electric furnace, sinter it at 1350°C for 10 hours, and cool it to room temperature.
[0031] Example 3
[0032] Weigh 50 parts of zircon bricks, 12 parts of zircon sand, 22 parts of fused zirconium corundum bricks, 7 parts of alumina, and 9 parts of silica sol-alumina composite binder. Break the fused zirconium corundum bricks into pieces and put them into a nylon jar. Use deionized water as the grinding medium and grind them in a planetary mill for 48 hours. After drying, pass through a 120-mesh sieve. Dry-mix zircon bricks, zircon sand, and fused zirconium corundum bricks for 2 minutes, then slowly add alumina and silica sol-alumina composite binder and wet-mix for 5 minutes, then pass through a 4-mesh sieve to obtain a mixture. Ram the mixture into a cylindrical embryo under a pressure of 20MPa. The embryo is dried at 125°C with the mold for 8 hours and demolded. After demolding, place it in an electric furnace, sinter it at 1400°C for 10 hours, and cool it to room temperature.
[0033] Example 4
[0034] Weigh 50 parts of zircon bricks, 15 parts of zircon sand, 20 parts of fused zirconium corundum bricks, 7 parts of alumina, and 8 parts of silica sol-alumina composite binder. Break the fused zirconium corundum bricks into pieces and put them into a nylon jar. Use deionized water as the grinding medium and grind them in a planetary mill for 48 hours. After drying, pass through a 120-mesh sieve. Dry-mix zircon bricks, zircon sand, and fused zirconium corundum bricks for 2 minutes, then slowly add alumina and silica sol-alumina composite binder and wet-mix for 3 minutes, then pass through a 4-mesh sieve to obtain a mixture. Ram the mixture into a cylindrical embryo under a pressure of 20MPa. The embryo is dried at 125°C with the mold for 8 hours and demolded. After demolding, place it in an electric furnace, sinter it at 1300°C for 10 hours, and cool it to room temperature.
[0035] Example 5
[0036] Weigh 48 parts of zircon bricks, 15 parts of zircon sand, 20 parts of fused zirconium corundum bricks, 7 parts of alumina, and 10 parts of silica sol-alumina composite binder. Break the fused zirconium corundum bricks into pieces and put them into a nylon jar. Use deionized water as the grinding medium and grind them in a planetary mill for 48 hours. After drying, pass through a 120-mesh sieve. Dry-mix zircon bricks, zircon sand, and fused zirconium corundum bricks for 3 minutes, then slowly add alumina and silica sol-alumina composite binder and wet-mix for 5 minutes, then pass through a 4-mesh sieve to obtain a mixture. Ram the mixture into a cylindrical embryo under a pressure of 20MPa. The embryo is dried at 125°C with the mold for 8 hours and demolded. After demolding, place it in an electric furnace, sinter it at 1250°C for 10 hours, and cool it to room temperature.
[0037] Example 6
[0038] Weigh 50 parts of zircon bricks, 15 parts of zircon sand, 20 parts of fused zirconium corundum bricks, 7 parts of alumina, and 8 parts of silica sol-alumina composite binder. Break the fused zirconium corundum bricks into pieces and put them into a nylon jar. Use deionized water as the grinding medium and grind them in a planetary mill for 48 hours. After drying, pass through a 120-mesh sieve. Dry-mix zircon bricks, zircon sand, and fused zirconium corundum bricks for 2 to 3 minutes, then slowly add additives and binders and wet-mix for 3 to 5 minutes, then pass through a 4-mesh sieve to obtain a mixture. Ram the mixture into a crucible-shaped embryo under a pressure of 20 MPa. The embryo is dried at 125°C with the mold for 8 hours and demolded. After demolding, place it in an electric furnace, sinter it at 1400°C for 10 hours, and cool it to room temperature.
[0039] Example 7
[0040] Weigh 50 parts of zircon bricks, 15 parts of zircon sand, 20 parts of fused zirconium corundum bricks, 7 parts of cerium oxide, and 8 parts of silica sol-alumina composite binder. Break the fused zirconium corundum bricks into pieces and put them into a nylon jar. Use deionized water as the grinding medium and grind them in a planetary mill for 48 hours. After drying, pass through a 120-mesh sieve. Dry-mix zircon bricks, zircon sand, and fused zirconium corundum bricks for 3 minutes, then slowly add cerium oxide and silica sol-alumina composite binder and wet-mix for 4 minutes, then pass through a 4-mesh sieve to obtain a mixture. Ram the mixture into a cylindrical embryo under a pressure of 20MPa. The embryo is dried at 125°C for 8 hours with the mold and demolded. After demolding, place it in an electric furnace, sinter it at 1250°C for 10 hours, and cool it to room temperature.
[0041] Example 8
[0042] Weigh 50 parts of zircon bricks, 15 parts of zircon sand, 20 parts of fused zirconium corundum bricks, 7 parts of boric acid, and 8 parts of silica sol-alumina composite binder. Break the fused zirconium corundum bricks into pieces and put them into a nylon jar. Use deionized water as the grinding medium and grind them in a planetary mill for 48 hours. After drying, pass through a 120-mesh sieve. Dry-mix zircon bricks, zircon sand, and fused zirconium corundum bricks for 3 minutes, then slowly add boric acid and silica sol-alumina composite binder and wet-mix for 4 minutes, then pass through a 4-mesh sieve to obtain a mixture. Ram the mixture into a crucible-shaped embryo under a pressure of 20MPa. The embryo is dried at 125°C with the mold for 8 hours and demolded. After demolding, place it in an electric furnace, sinter it at 1250°C for 10 hours, and cool it to room temperature.
[0043] Example 9
[0044] Weigh 50 parts of zircon bricks, 15 parts of zircon sand, 20 parts of fused zirconium corundum bricks, 7 parts of magnesium oxide, and 8 parts of silica sol-alumina composite binder. Break the fused zirconium corundum bricks into pieces and put them into a nylon jar. Use deionized water as the grinding medium, grind them in a planetary mill for 48 hours, and pass through a 120-mesh sieve after drying. Dry-mix zircon bricks, zircon sand, and fused zirconium corundum bricks for 2 minutes, then slowly add magnesium oxide and silica sol-alumina composite binder and wet-mix for 5 minutes, then pass through a 4-mesh sieve to obtain a mixture. Ram the mixture into a cylindrical embryo under a pressure of 20MPa. The embryo is dried at 125°C with the mold for 8 hours and demolded. After demolding, place it in an electric furnace, sinter it at 1250°C for 10 hours, and cool it to room temperature.
[0045] Comparative Example 1
[0046] Weigh 68 parts of zircon brick, 15 parts of zircon sand, 9 parts of zircon powder, and 8 parts of industrial phosphoric acid, wet mix for 5 minutes, and then pass through a 4-mesh sieve to obtain a mixed material. Ramming and shaping. Curing at 300°C for 24 hours, and finally heat treatment at 1250°C for 3 hours.
[0047] Comparative Example 2
[0048] Weigh 68 parts of zircon bricks, 15 parts of zircon sand, 9 parts of zircon powder, and 8 parts of industrial phosphoric acid, wet mix for 5 minutes, and then pass through a 4-mesh sieve to obtain a mixture. Ramming and forming. Dry the embryo with the mold at 125°C for 8 hours and demold. After demolding, place it in an electric furnace, sinter it at 1250°C for 10 hours, and cool it to room temperature.
[0049] Comparative Example 3
[0050] Weigh 60 parts of zircon bricks, 15 parts of zircon sand, 9 parts of zircon powder, 8 parts of industrial phosphoric acid, and 8 parts of alumina, wet mix for 5 minutes, and then pass through a 4-mesh sieve to obtain a mixture. Ramming and forming. Dry the embryo with the mold at 125°C for 8 hours and demold. After demolding, place it in an electric furnace, sinter it at 1250°C for 10 hours, and cool it to room temperature.
[0051] Performance Testing
[0052] According to the “Test Methods for Refractory Materials” and “Physical Test Methods for Refractory Materials”, the linear change rate, flexural strength, compressive strength, bulk density, water absorption and apparent porosity of the samples are tested.
[0053] Table 1
[0054]
[0055] The technical standards of zircon ramming material are: linear change rate ≤-0.3%, compressive strength ≥50MPa, bulk density ≥3.45g / cm 3 The zircon ramming materials obtained by Examples 1 to 9 of the present invention all meet the indicators and have low porosity. When the additive is alumina, the zircon ramming materials obtained have a smaller linear change rate, which indicates that alumina can reduce the high-temperature volume shrinkage of the ramming materials.
[0056] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.
Claims
1. A method for preparing zircon ramming material for a glass kiln, comprising the following steps: (1) Ingredients: Weigh zircon bricks, zircon sand, fused-cast zirconium corundum bricks, additives and binders according to the number of parts. Break the fused-cast zirconium corundum bricks into pieces and put them into a nylon can. Grind them in a planetary mill for 48 hours, dry them and sieve them. (2) Mixing: dry-mix zircon bricks, zircon sand and fused zirconium corundum bricks for 2 to 3 minutes, then slowly add additives and binders and wet-mix for 3 to 5 minutes, and then sieve to obtain a mixed material. (3) Molding: The mixed material in step (2) is pounded into a crucible-shaped or cylindrical embryo under a pressure of 20 MPa. (4) Drying: The embryo is dried with the mold at 125°C for 8 hours and then demolded. (5) Sintering: After demoulding, place it in an electric furnace and sinter it at 1250-1400°C for 10 hours, then cool it to room temperature.
2. The method for preparing zircon ramming material for glass furnace according to claim 1, characterized in that: 45-50 parts of zircon bricks, 12-18 parts of zircon sand, 15-23 parts of fused-cast zirconium corundum bricks, 7-14 parts of additives and 8-15 parts of binders.
3. The method for preparing zircon ramming material for glass furnace according to claim 2, characterized in that: The additive is one or more of alumina, magnesium oxide, boric acid and cerium oxide, and the binder is a silica sol-alumina composite binder.
4. The method for preparing zircon ramming material for glass furnace according to claim 1, characterized in that: The operating parameters of the planetary mill during grinding in step (1) are: orbital speed 250 r / min, rotational speed 200 r / min, ball: material = 15:
1.
5. The method for preparing zircon ramming material for glass furnace according to claim 1, characterized in that: In step (1), a certain amount of deionized water is added as a grinding medium to improve the grinding efficiency, and the mixture is dried and passed through a 120-mesh sieve.
6. The method for preparing zircon ramming material for glass furnace according to claim 1, characterized in that: After mixing in step (2), pass through a 4-mesh sieve.
7. The method for preparing zircon ramming material for glass furnace according to claim 1, characterized in that: Step (3) The mold size is φ70mm×70mm.
8. A zircon ramming mass for a glass furnace, characterized in that: The zircon ramming material is prepared by the method described in any one of claims 1 to 7.
Citation Information
Patent Citations
Refractory materials and refractory equipment for aluminum alloy melt casting, and method for preparing refractory equipment
CN101423400A
Method for preparing zircon brick from compact zircon aggregate
CN107935608A
Grouting slurry for blowpipe, grouting type blowpipe and preparation method of grouting type blowpipe
CN114230354A
Compact zirconite brick and preparation method thereof
CN114702323A
Refractory dry-ramming mix based on zirconia for lining crucible induction furnaces
EP0049366A1
Cited By
Zirconium amorphous material for sealing layer at bottom of glass melting furnace and preparation method of zirconium amorphous material
CN119841638A
Zirconium-based amorphous material for the bottom sealing layer of glass melting furnace and its preparation method
CN119841638B